Involvement of organic cation transporter 3 (Oct3/Slc22a3) in the bioavailability and pharmacokinetics of antidiabetic metformin in mice. Issue 5 (October 2016) - Shirasaka, Yoshiyuki; Lee, Nora; Zha, Weibin; Wagner, David; Wang, Joanne
Abstract: Metformin is widely used for the treatment of type II diabetes mellitus. It was reported to be substrate of OCT3/Oct3, which is expressed in the brush boarder membrane of the enterocytes. However, the role of OCT3/Oct3 in the intestinal absorption process of metformin remains obscure. In the present study, we aimed to clarify the impact of Oct3 on the oral bioavailability and pharmacokinetics of metformin in mice, by means of in vivo pharmacokinetic study using wild-type (Oct3 +/+ ) and Oct3-knockout (Oct3 −/− ) mice. When metformin (8.0 mg/kg) was intravenously administered to male Oct3 +/+ and Oct3 −/− mice, AUC0–∞ of metformin was evaluated to be 659 ± 133 μg h/mL and 734 ± 213 μg h/mL, respectively. In the case of orally administered metformin (15 mg/kg), AUC0–∞ was 578 ± 158 μg h/mL and 449 ± 101 μg h/mL in Oct3 +/+ and Oct3 −/− mice, respectively. Based on these pharmacokinetic parameters, absolute bioavailability ( F ) of metformin in Oct3 +/+ mice was evaluated as 46.8%, and it was significantly decreased to 32.6% in Oct3 −/− mice. Taking into account the fact that metformin undergoes negligible metabolism, these results imply that intestinal absorption of metformin is mediated at least in part by Oct3 in mice. Graphical abstract: